REORIENTASI POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANG DI INDONESIA - Heriyono Tardjono (Prima Center Indonesia, 2016)
Indonesia is a legal state (rechtstaat), not a power state (machstaat). This study aims at addressing following problems; first, how is the political law orientation of lawmaking process in Philipe Nonet dan Philip Selznick’s Responsive Law theory approach?; second, how is the correlation of Pancasila and political law in lawmaking process?; third, how is the reorientation of political law in lawmaking process in Indonesia?. The findings of the study showed that the direction or orientation of lawmaking process in Indonesia had changed from autonomy in Old Order regime became repressive in New Order regime and further reinstalled to be autonomy. Having regard to the values embedded in Pancasila and the constitutional mandate, it can be said that the Indonesia does not embrace Capitalist-Individualist ideology which put more emphasis on individual rights, but rather on communal rights by not overriding the rights of individuals. Pancasila is an ideolgy that provides the middle ground, which on the one side accentuates the communal rights, but on the other side remain protecting the individual rights. This stance is known as Monodualism. It is required the reorientation in lawmaking process in Indonesia which means the reversion of its direction or tendency. The lawmaker should reenact the values of Pancasila and the Constitution of Republic of Indonesia in the making of law.Keywords: political law orientation; legal state